Ultrafast Wavelength Jumping and Wavelength Adjustment With Low Current Using Monolithically Integrated FML for Long-Reach UDWDM-PON - Guang Yong Chu; Josep Prat (IEEE Photonics Journal)
Ultrafast wavelength jumping at optical network units (ONUs) for an access network with frequency modulated lasers (FMLs) is demonstrated. This FML consists of an intracavity tunable phase section and filtering gain section. It provides a total of 4.2 nm tuning range with fast wavelength jumping (2.2 nm in 1 $ μ$ s) and fast adjustment (1.3 nm in 1.8 ns), providing a candidate for the fast tuning ONU for coherent ultradense wavelength-division multiplexing passive optical networks (WDM-PONs).